The Use of “Rumah Belajar” in PAI Learning during Covid-19 at Marhamah Elementary School - Liza Warni; Riki Saputra; Aguswan Rasyid (Program Pascasarjana UMSB, 2021)
This research was conducted to determine the implementation of Islamic Education learning using learning house media for fifth grade students at SD Plus Marhamah Padang. This study was motivated by the widespread use of electronic media such as; cellphones, laptops, and computers as well as a higher tendency of students to electronic media compared to books and also the implementation of online learning during the Covid-19 pandemic. This study is intended to see the impact of the implementation of Islamic Education learning using learning house media, especially by using the main features available in learning house media such as learning resource features, virtual class features, question banks and virtual laboratories during the Covid-19 pandemic. The results of the use of learning house media show several things including; The use of learning resource features on learning home media can be used as an effective medium and also a solution to educational problems that occurred during the pandemic, the use of virtual class features is one of the features used as a tool to support the implementation of Islamic Education learning because this feature can be used as a means In the formation of a special class guided by the teacher concerned to carry out online and offline learning, the use of the question bank feature is one of the media that can create more effective learning activities when implementing remote learning, while the use of virtual laboratory features in Islamic Education learning in SD Plus Marhamah Padang. Islamic education teachers have not used this feature as a medium to support the implementation of learning